2008
DOI: 10.1097/01.jnr.0000387292.99300.92
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between TV/Computer Time and Adolescents' Health-Promoting Behavior

Abstract: Television and computers provide significant benefits for learning about the world. Some studies have linked excessive television (TV) watching or computer game playing to disadvantage of health status or some unhealthy behavior among adolescents. However, the relationships between watching TV/playing computer games and adolescents adopting health promoting behavior were limited. This study aimed to discover the relationship between time spent on watching TV and on leisure use of computers and adolescents' hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
(43 reference statements)
0
10
1
1
Order By: Relevance
“…Previous studies have shown that skipping breakfast and spending more than four hours each day watching TV and playing computer games among adolescents are negatively associated with adolescent health status (e.g., obesity) and with health-related behaviors, including school achievement [12, 13, 30]. We therefore focused on three indicators of unhealthy lifestyle: (1) being overweight or obese, (2) frequently skipping breakfast, and (3) excessive time spent watching TV or playing computer games.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that skipping breakfast and spending more than four hours each day watching TV and playing computer games among adolescents are negatively associated with adolescent health status (e.g., obesity) and with health-related behaviors, including school achievement [12, 13, 30]. We therefore focused on three indicators of unhealthy lifestyle: (1) being overweight or obese, (2) frequently skipping breakfast, and (3) excessive time spent watching TV or playing computer games.…”
Section: Resultsmentioning
confidence: 99%
“…We defined time spent playing on the computer as “except for school requirements (e.g., assignments) or searching for academic information, on weekdays I used the computer for playing games or chatting, in both home and cyber café settings”. We defined TV watching by the statement, “except for school requirements, the time between turning on and turning off the TV set on weekdays” [13]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Di¤er taraftan ülkemizin de içinde bulundu¤u farkl› ülkelerde yap›lan araflt›rmalarda kentsel alanda yaflayan çocuklar›n daha fazla TV izledi¤i gösterilmifltir (26,29,47,51). Tersine, k›rsal alandaki çocuk-lar aras›nda TV izleme sürelerinin daha uzun oldu¤unu gös-teren yay›nlar da vard›r (54,55). Uzun süre televizyon izleme ile fliflmanl›k ve besin de¤eri düflük, enerji oran› yüksek yiyeceklerin tüketilmesi aras›nda iliflki oldu¤u çok say›da araflt›rmac› taraf›ndan gösterilmifltir (2,5,7,54,56,57).…”
Section: Tart›flmaunclassified
“…Health-promoting activities seek to strengthen the host through a variety of approaches in the form of health education, lifestyle modification, behavior change, environment modification, and nutrition intervention (10). Health-promoting behavior is defined as the first level of primary prevention, beginning with healthy adolescents who seek to improve their lifestyles to achieve better health (11).…”
Section: Introductionmentioning
confidence: 99%